Nonremission After Electroconvulsive Therapy in Individuals With Major Depression: Role of Borderline Personality Disorder. Issue 4 (29th December 2022) - Hein, Matthieu; Mungo, Anaïs; Loas, Gwenolé
Abstract : Objectives: The aim of the present study was to investigate the risk of nonremission following electroconvulsive therapy (ECT), as associated with borderline personality disorder, in individuals with major depression in the context of the contradictory data available in the literature. Methods: We analyzed demographic and clinical data from 210 individuals with major depression who were treated with ECT. Study participants were recruited from the medical records database of the Psychiatry Department at Erasme Hospital. Only individuals with major depression who were in remission, as demonstrated during the systematic psychiatric interview performed at the end of ECT (ie, with a >60% reduction in their 24-item Hamilton Depression Rating Scale score, combined with a score of <10), were included in the "remission" group. Logistic regression analyses were used to determine the risk of nonremission following ECT. Results: Nonremission following ECT occurred frequently (42.9%) in our sample. Moreover, after adjusting for major confounding factors, multivariate logistic regression analyses demonstrated that borderline personality disorder was a risk factor for nonremission following ECT in individuals with major depression. Conclusions: We demonstrated that borderline personality disorder was associated with a higher risk of nonremission following ECT in individuals with major depression. This finding seems to justify more systematic screening as well as more adequate management of this personality disorder in individuals with major depression who are treated with ECT to allow for attaining better remission rates in this subpopulation.